2013
DOI: 10.1108/03074801311304023
|View full text |Cite
|
Sign up to set email alerts
|

Online access to higher education on YouTubeEDU

Abstract: Purpose -The purpose of this one-year longitudinal study is to examine the usage and production of educational videos on YouTubeEDU, an open, video-sharing, educational area of YouTube established in 2009 and used primarily by institutions of higher education. The aim of the YouTubeEDU project is to provide free global access to higher education videos. Analysis from a library science perspective is valuable to further development of YouTubeEDU. Design/methodology/approach -From August 2010 to July 2011, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Public relations texts are a successful way of getting into these news media and their content often directly competes with editorial content by science journalists (Vogler and Schäfer, 2020). This finding also seems to apply to YouTube, where a study found that videos posted by universities mostly aim at portraying the institution in a good light (Chen and Burns Gilchrist, 2013). The only study we know of that quantitatively compared between individuals and institutions on YouTube is the one previously mentioned by Muñoz Morcillo et al (2019).…”
supporting
confidence: 54%
“…Public relations texts are a successful way of getting into these news media and their content often directly competes with editorial content by science journalists (Vogler and Schäfer, 2020). This finding also seems to apply to YouTube, where a study found that videos posted by universities mostly aim at portraying the institution in a good light (Chen and Burns Gilchrist, 2013). The only study we know of that quantitatively compared between individuals and institutions on YouTube is the one previously mentioned by Muñoz Morcillo et al (2019).…”
supporting
confidence: 54%
“…In their study, Chen and Gilchrist (2013), also found several applications of digital video content for individual improvements, they also suggested that online contents are appropriate for scholars, who have previous knowledge of those. So, it seems due to having little experience and adequate expertise with educational tools, students faced such a level of discomfort or psychological inertia, which they overcome gradually.…”
Section: Analysis Research Findings and Discussionmentioning
confidence: 91%
“…Literature provides evidence of social media usage as an essential learning component for academic communities in higher education (Chen & Gilchrist, 2013). Social media has facilitated not only students but also researchers and educators by providing them with a platform to collaborate and communicate.…”
Section: Theoretical Backgroundmentioning
confidence: 99%